Osteomyelitis Infection of Mycobacterium marinum: A Case Report and Literature Review - Hao H. Nguyen; Nada Fadul; Muhammad S. Ashraf; Dawd S. Siraj (Case Reports in Infectious Diseases)
Mycobacterium marinum (M. marinum) is a ubiquitous waterborne organism that grows optimally at temperatures around 30°C. It is a nontuberculous Mycobacterium found in nonchlorinated water with worldwide prevalence. It is the most common atypical Mycobacterium that causes opportunistic infection in humans. M. marinum can cause superficial infections and localized invasive infections in humans, with the hands being the sites most frequently affected. It can cause skin lesions, which are either single, papulonodular lesions, confined to an extremity, or may resemble cutaneous sporotrichosis. This infection can also cause deeper infections including tenosynovitis, bursitis, arthritis, and osteomyelitis. Disseminated infections and visceral involvements have been reported in immunocompromised patients. We here report a case of severe deep soft tissue infection with necrotizing fasciitis and osteomyelitis of the left upper extremity (LUE) caused by M. marinum in an immunocompromised patient.